Asuhan Kebidanan Continuity of Care (Coc) Pada Ny "S" di Praktik Mandiri Bidan Kasih Bunda Kec. Plakat Tinggi, Kab. Musi Banyuasin - Riski, Merisa; Septiani, Tety; Felina, Firna (Madani: Jurnal Ilmiah Multidisiplin, 2024)
According to WHO, 75% of neonatal deaths in the first week of life and 1 million neonatal deaths in the first 24 hours of life are caused by prematurity, asphyxia, infection, birth defects. IMR in 2020 has reached 21 deaths per 100 thousand births, however with a slow downward trend it is estimated that it will not reach the SDGs target in 2030 of 12 infant deaths per 100 thousand births. The number of maternal deaths in South Sumatra Province in 2021 was 131 people (with an MMR of 85 people per 100,000 live births), an increase from 84 people in 2020. The highest cause of death in mothers was other causes, namely 52 people (40%). This research method uses descriptive reports aimed at seeing a picture of phenomena that occur in a certain population. The target of taking this case study was Mrs "S" G2P1A0 Pregnant 38 Weeks 5 Days Normally at the Independent Practice of Midwife Kasih Bunda, Plakat Tinggi District, Musi Banyuasin Regency in 2024. Comprehensive midwifery care for Mrs "S" carried out data studies, namely subjective data and objective data, establishing a diagnosis and evaluating the care provided according to midwifery care measures, comparing the suitability and differences between theory and practice. In providing pregnancy care, 6 visits were carried out, childbirth care starting from stage I to IV, newborns at 1 hour of age, neonates and the postpartum period at 6 hours and 6 days of age, where the results were that there were no abnormalities.